Abnormal cisatracurium pharmacodynamics and pharmacokinetics among patients with severe aortic regurgitation during anesthetic induction - Huang, Xiaocong (BMC Anesthesiol, 2020)
BACKGROUND: This study was designed to examine whether severe aortic regurgitation will affect the pharmacodynamics (PD) and pharmacokinetics (PK) of cisatracurium during anesthetic induction. METHODS: A total of 32 patients were divided into two groups: the AR group (n = 16) and the control group (n = 16). Arterial blood samples were drawn before and at 1, 2, 4, 6, 8, 10, 16 and 20 min after intravenous injection of 0.15 mg/kg cisatracurium. TOF tests were applied to determine the onset time of maximal muscle relaxation. The concentration of cisatracurium in plasma was determined by high-performance liquid chromatography. RESULTS: The onset time to maximal neuromuscular block was prolonged from 2.07 ± 0.08 min to 4.03 ± 0.14 min, which indicated that the PD responses to cisatracurium were significantly delayed in the AR group (P < 0.05) compared to the control group. A conventional two-compartment PK model showed a higher plasma concentration of cisatracurium among the AR group with markedly reduced intercompartment transfer rate (K(12) = 0.19 ± 0.02 and K(21) = 0.11 ± 0.01 in the AR group vs. K(12=)0.26 ± 0.01 and K(21) = 0.19 ± 0.01 in the control group, P < 0.01) compared to the control group. CONCLUSION: Backward blood flow during diastole in severe AR impaired distribution of cisatracurium from the central compartment to the peripheral compartment, which accounted for the lagged PD responses. Findings in this study underlie the importance of muscular blockade monitoring among patients with severe aortic regurgitation during anesthetic induction. REGISTRATION: Name of the registry: Abnormal Cisatracurium Pharmacodynamics and Pharmacokinetics among Patients with Severe Aortic Regurgitation during Anesthetic Induction. Trial registration number: ChiCTR1800019654. Date of registration: November 20th 2018.